Regionalization of pediatric emergency care in Korea - Do Kyun Kim (Korean Pediatric Society, 2011)
In order to care for an ill or injured child, it is crucial that every emergency department (ED) has a minimum set of personnel and resources because the majority of children are brought to the geographically nearest ED. In addition to adequate preparation for basic pediatric emergency care, a comprehensive, specialized healthcare system should be in place for a critically-ill or injured victim. Regionalization of healthcare means a system providing high-quality and cost-effective care for victims who present with alow frequency, but critical condition, such as multiple trauma or cardiac arrest. Within the pediatric field, neonatal intensive care and pediatric trauma care are good examples of regionalization. For successful regionalized pediatric emergency care, all aspects of a pediatric emergency system, from pre-hospital field to hospital care, should be categorized and coordinated. Efforts to set up the pediatric emergency care regionalization program based on a nationwide healthcare system are urgently needed in Korea.